ANALISIS MANAJEMEN KEPALA SEKOLAH DALAM MEMPEROLEH PRESTASI KOMPETISI BAHASA DAN SASTRA JAWA TINGKAT PROVINSI DI SD NEGERI 4 WATES - Priyono; Sunarto; Mulyanto (STKIP Subang, 2023)
This study aims to analyze the management of school principals in obtaining achievements in Javanese language and literature competitions at the provincial level, to analyze the obstacles and supports in applying management to obtain achievements in Javanese language and literature competitions at the provincial level, to analyze the achievement of school principals in obtaining achievements in language competitions and Javanese literature at the provincial level. This study uses a qualitative approach. Data was collected using interviews, observation, and documentation. Data were analyzed using inductive analysis. The results of the study show that the management of school principals in obtaining provincial-level Javanese language and literature competition achievements is planning the implementation of the independent learning curriculum and K13, planning the allocation of funds for the preparation of Javanese language and literature competitions, planning students who will be included in competitions, organizing teacher human resources in the form of appointing several teachers to accompany students participating in Javanese language and literature competitions, organizing human resources from the Alang-alang studio as a support studio for training students participating in Javanese language and literature competitions, organizing teaching materials in the form of selecting teaching materials for students according to technical guidelines, organizing time in the form of conveying student training schedules , Mobilization by giving teacher orders to conduct student coaching, mobilization in the form of giving teacher orders to compile material according to the technical guidelines for HR Control, Cost control by always reviewing expenses, Control of teaching materials in the form of always reviewing so that the material delivered is in accordance with the technical guidelines for competition, and Time control so that students can master the material on time before the Javanese language and literature competition is held. Obstacles in applying management to obtain achievements in the Javanese language and literature competition at the provincial level are the limited number of human resources which results in insufficient accompanying teachers to accompany students who will conduct Javanese language and literature competitions. Funding limitations forced schools to think about how to collect funds other than BOS to support activities to prepare Javanese language and literature competitions. Material Barriers, Technological Barriers, Method Barriers, Time Barriers. Supporting factors are supporting factors from human resources, gifted students, competent trainers, dedicated teachers, parents of students who are willing to contribute funds, supporting factors from parents who have provided their own teaching methods, students who have a lot of free time.